Intelligent systems and decision making for risk analysis and crisis response : proceedings of the 4th International Conference on Risk Analysis and Crisis Response, Istanbul, Turkey, 27-29 August, 2013 /: proceedings of the 4th International Conference on Risk Analysis and Crisis Response, Istanbul, Turkey, 27-29 August, 2013. ([2013]) - Unknown
No abstract available